PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL TERHADAP MOTIVASI BELAJAR SISWA SD NEGERI 06 PADANG - Ria Satini; Asri Wahyuni Sari; Najmi Hayati; Risa Yulisna; Hasnul Fikri (Study program PGSD FKIP Universitas Bung Hatta, 2026)
The purpose of this study is to describe how the use of digital educational media affects students’ motivation to learn in elementary school. This study employs a descriptive qualitative method. Data collection was conducted through observation, interviews, and documentation. The subjects of this study were students from SD Negeri 06 Padang. The results of the study show that the use of digital educational media, such as educational videos, interactive educational applications, and multimedia presentations, has a significant positive impact on students’ enthusiasm for learning. Students showed greater enthusiasm, asked questions more frequently, and were more focused while learning compared to traditional teaching methods. However, several obstacles were also identified, including limited technological resources, unstable internet connections, and a lack of digital skills among teachers. This study recommends providing schools with technological resources and implementing ongoing teacher training programs to maximize the use of digital media in the teaching and learning process.